Level of Citizen Participation in Pedro de Valdivia Family Health Care Center users, Concepción, Chile 2019 - Gay, Nicole; Araya, Carlos (Revista Chilena de Salud Pública, 2022)
Introduction: Citizen Participation is one of the fundamental pillars to achieve legitimate and stable governance; it is also considered one of the social determinants of health and the guiding axis of primary health care. The main objective of this research is to determine the level of Citizen Participation (CP) in users of the Family Health Center (CESFAM) Pedro de Valdivia, according to age, sex, level of schooling, religion and socioeconomic level in the Associative-Opinionary, Electoral dimensions, Partisan and Civic. Materials and Methods: A quantitative, observational, cross-sectional study with a descriptive scope was carried out. The Participation Behavior Questionnaire (CCP) was applied as an instrument to analyze CT behaviors, measuring the Electoral, Associative-opinionary, Partisan and Civic dimensions to 213 users who agreed to participate in this study. Results: The PC level corresponds to a medium level, with only significant differences in users older than 65 years where this level is high. The results found mark the differences in the levels of participation in the Partisan and Associative-Opinionary Dimensions that correspond to a low level, unlike the Civic and Electoral Dimensions that are at a high level. Discussion: Work should be done to enhance PC, especially in young people and providing equitable spaces with a gender approach, promoting the guiding axis in primary health care.